The First Brazilian Fashion Show held in 1952, In the City of São Paulo, by Newly Immigrant Italians - do Prado, Luís André (ZoneModa Journal, 2021)
This article rescues and analyzes the facts and characters involved in the promotion of the First Brazilian Fashion Show, which took place on November 6, 1952 at the São Paulo Museum of Art (MASP), by an Italian couple who had recently emigrated to Brazil: Pietro Maria Bardi and Achillina (or Lina) Bo Bardi, he journalist and art dealer, she architect. The social, economic and ideological motivations that made possible this pioneering and extemporaneous event in the history of fashion in the country are highlighted, as well as its oblique relationships with the emergence of the field of fashion creation in Brazil and Italy.